Azido‐Functionalized 5′ Cap Analogues for the Preparation of Translationally Active mRNAs Suitable for Fluorescent Labeling in Living Cells. (7th November 2017) - Mamot, Adam; Sikorski, Pawel J.; Warminski, Marcin; Kowalska, Joanna; Jemielity, Jacek
Abstract: The 7‐methylguanosine (m 7 G) cap structure is a unique feature present at the 5′ ends of messenger RNAs (mRNAs), and it can be subjected to extensive modifications, resulting in alterations to mRNA properties (e.g. translatability, susceptibility to degradation). It also can provide molecular tools to study mRNA metabolism. We developed new mRNA 5′ cap analogues that enable the site‐specific labeling of RNA at the 5′ end using strain‐promoted azide–alkyne cycloaddition (SPAAC) without disrupting the basic function of mRNA in protein biosynthesis. Some of these azide‐functionalized compounds are equipped with additional modifications to augment mRNA properties. The application of these tools was demonstrated by labeling translationally active mRNAs in living cells.